Preliminary study on shear strength of reinforced concrete beams by nonlinear analysis - Balakrishna, M.N.; Vidivelli, B. (Journal of Structural Engineering, 2025)
The exact prediction of load carrying capacity of reinforced concrete beam with their shear failure, and crack pattern has not yet been clearly defined although lots of research was conducted. However, as more and more knowledge and understanding is gained through continuing experimental and analytical studies, a day may come when a satisfactory design procedure may be developed by using nonlinear finite element analysis. The objectives of this study were to investigate the influence of following factors on shear strength of reinforced concrete beam in turn to study shear failure behavior, and load carrying capacity of beams by using finite element analysis: i) Concrete strength; ii) Tensile reinforcement ratio; iii) Shear span-effective depth ratio; iv) Size of beam. In this research work, beams of different cross sections, main longitudinal reinforcement ratios, and concrete compressive strengths were investigated by considering different load cases. From this research work it is concluded that, shear strength of reinforced concrete beams increased with the increase of concrete compressive strength (lesser shear span-effective depth ratio), and tensile reinforcement ratio. Also nominal shear stress of reinforced concrete beams increased with the increase of tensile reinforcement ratio and decreased with the increase in beam size.